Integrative and Complementary Practices in the treatment of anxiety triggered by Covid-19: A narrative review (Research, Society and Development, 2024)
Complementary Integrative Practices (ICPs) have the main objective of promoting self-care and awakening in individuals an awareness of what health is in its entirety. The therapeutic techniques used in ICPs act efficiently in the treatment of anxiety in patients affected by the Coronavirus, as demonstrated by scientific literature. The objectives of this study are to explain the mental health disorders resulting from the Covid-19 pandemic and list the role of ICPs in health promotion, prevention, and treatment of these conditions, emphasizing homeopathy, phytotherapy, acupuncture, aromatherapy, music Therapy, and meditation. The study found that ICPs significantly alleviated anxiety and depression, reduced the demand for medications, and shortened hospital stays, highlighting their potential as low-risk, accessible adjuncts to conventional treatments. Further research is needed to optimize their application in clinical settings.